THE EFFECT OF PRICE PERCEPTION AND BRAND AWARENESS ON SERVICE QUALITY MEDIATED BY PURCHASING DECISIONS : (Study Case on PT. Maybank Indonesia Finance Credit Products) - Melitina Tecoalu; Hery Winoto Tj; Ferdian Ferdian (ID Solutions, 2021)
The finance company industry experienced much pressure in 2020 due to the covid-19 pandemic, this condition made business activities and social life almost stopped. This research was conducted at PT. Maybank Indonesia Finance is one of the financing companies in Indonesia that is currently proliferating. Purchasing decisions have an essential meaning for a financial institution because credit is one of the directives of funding by financial institutions to people who want to get an item on credit as the institution's main business. In determining a decision to purchase products and services, consumers perceive the goods and services they buy, such as the perception of the price of an item or service in making a purchase, and consumers can recognize the company's brand awareness. This research was conducted by nonprobability sampling method with purposive sampling type. Researchers distributed questionnaires to 100 Maybank Finance consumer respondents in Indonesia who had purchased Maybank Finance car loans in 2018-2020. The results of the analysis conclude that price perception has a positive and significant effect on purchasing decisions. Brand awareness has a positive and significant effect on credit purchasing decisions. Price perception has a positive and significant effect on service quality. Brand awareness has a positive and significant effect on service quality. Service quality has no positive and significant effect on purchasing decisions at Maybank Finance. Service quality mediating between brand awareness and purchasing decisions is not significant.